2012
DOI: 10.1371/journal.pone.0051062
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pseudomonas aeruginosa Cell Envelope Proteome by Capture of Surface-Exposed Proteins on Activated Magnetic Nanoparticles

Abstract: We report on specific magneto-capturing followed by Multidimensional Protein Identification Technology (MudPIT) for the analysis of surface-exposed proteins of intact cells of the bacterial opportunistic pathogen Pseudomonas aeruginosa. The magneto-separation of cell envelope fragments from the soluble cytoplasmic fraction allowed the MudPIT identification of the captured and neighboring proteins. Remarkably, we identified 63 proteins captured directly by nanoparticles and 67 proteins embedded in the cell enve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Proteomic analysis can provide further insights into the effects of nanomaterials on cells, such as their effects on membrane proteins after exposure to silver nanoparticles . Recently, high‐throughput liquid chromatography coupled with mass spectrometry methods have allowed efficient analysis of cell proteome and advancement in mass spectrometry has substantially increased the number of proteins that can be accurately identified and quantified . Such high‐throughput proteomic analysis represents major improvements over traditional methods and is expected to be more widely applied to study the antimicrobial mechanisms of nanomaterials.…”
Section: Genomics Transcriptomics and Proteomics Investigationsmentioning
confidence: 99%
“…Proteomic analysis can provide further insights into the effects of nanomaterials on cells, such as their effects on membrane proteins after exposure to silver nanoparticles . Recently, high‐throughput liquid chromatography coupled with mass spectrometry methods have allowed efficient analysis of cell proteome and advancement in mass spectrometry has substantially increased the number of proteins that can be accurately identified and quantified . Such high‐throughput proteomic analysis represents major improvements over traditional methods and is expected to be more widely applied to study the antimicrobial mechanisms of nanomaterials.…”
Section: Genomics Transcriptomics and Proteomics Investigationsmentioning
confidence: 99%
“…Due to the relevant role of the envelope-associated proteins, in the last two decades different studies aimed to characterize the P. aeruginosa envelope proteome. Most of them focused on OM [7][8][9][10] and global membrane [11][12][13], while a lesser number analyzed proteins from periplasmic space [14] and IM [15]. Some of these studies were based on two-dimensional (2-D) gel electrophoresis protein separation [7,8,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…High-apparent affinity high capacity IgG were found to extensively cross-react with the closely related HK-EB. This indicated that these antibodies recognized epitopes present at high density and which seem similar in Escherichia and Salmonella , possibly due to their common features in LPS 40 42 . However, and as expected, less cross-reactivity (yet still a considerable amount) was found when these antibodies were assayed against HK-PA, an evolutionarily more distant Gram-negative bacteria (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…4d ), making the immunodominant LPS a likely candidate antigen. LPS are strain-specific in their glycosylation, yet many variants also share similarities and conserved epitopes 40 42 . Consequently, we were interested in identifying whether the mice immunized with a specific bacteria species produced more specific or cross-reactive antibodies that might interact with other bacteria.…”
Section: Resultsmentioning
confidence: 99%